Reliability and validity of two computerised occlusion analysis systems. (March 2022) - Zhao, Zhe; Wang, Qing; Zheng, Xiuli; An, Na; Zhou, Ming; Niu, Lina; Tay, Franklin R.; Chen, Jihua; Wang, Fu
Abstract: Objectives: The present in vitro study evaluated the reliability and validity of two computerised occlusion analysis systems. Methods: Three occlusion analysis methods were evaluated. The methods included one traditional method (scanning of articulating paper marks (SAP)) and two computerised systems: (dental prescale occlusion analysis system (DPO) and a modified virtual occlusion construction method (VOC)). For reliability evaluation, the occlusion of an articulator-mounted anatomical dentoform was analysed ten times with each of the three methods. Occlusal contact areas and contact number values were obtained and the coefficient of variation (CoV) of each method was compared. For validity evaluation, resin casts of the dentition of 10 human subjects were used for analysis. Paired t-tests, regression analysis and Bland-Altman analysis were used to evaluate the difference and agreement amongst the three methods. Results: The CoV values of occlusal contact areas from the entire dentition were in the order: SAP (5.7%) < DPO (12.7%) < VOC (15.6%). Higher values was found in the anterior teeth (19.8–40.8%). Significant differences were identified in the occlusal contact areas of the entire dentition and posterior teeth obtained from SAP and DPO; a significant correlation was detected between the two methods ( P < 0.01). Bland-Altman agreement analysis indicated good agreement between SAP and VOC. Conclusions: Both DPO and VOC have good reliability and validity. They are potential alternatives for analysis of occlusal contacts. Clinical significance: The dental prescale occlusion analysis system and the modified virtual occlusion constructed method combine convenience with the objectivity of digital technology. These computerised occlusion analysis systems may be used for quantitative analysis of occlusal contacts in clinical practice, with good reliability and validity.